Direct oral anticoagulation versus no therapy or antiplatelet for stroke prevention in patients with atrial fibrillation and history of intracranial hemorrhage: a systematic review and meta-analysis - Sablot, Denis; Gaillard, Nicolas; Belahsen, Faouzi; Lamelo, Sara Rivas; Dumitrana, Adrian; Plantard, Carole; Daghmouri, Mohamed Aziz; Chaouch, Mohamed Ali (Frontiers in Medicine, 2025)
BackgroundPatients with atrial fibrillation and a history of intracranial hemorrhage (ICH) face a dilemma when resuming anticoagulation therapy due to the risk of ICH recurrence versus the need for Ischemic stroke (IS) prevention. This study aims to evaluate the safety and efficacy of direct oral anticoagulants (DOAC) compared to no therapy or antiplatelets in these patients.MethodsWe conducted a systematic review and meta-analysis following PRISMA 2020 guidelines. Electronic searches were performed in multiple databases (Cochrane, PubMed, Web of Science, Embase, Google Scholar, Scopus) up to March 1, 2024. We included randomized controlled trials (RCTs) and controlled clinical trials (CCTs) involving patients with atrial fibrillation and prior ICH. Studies compared the group with no therapy or antiplatelets (no-DOAC group). Outcomes assessed included mortality, IS, ICH recurrence, and major bleeding events.ResultsFifteen studies (8,318 patients) met the inclusion criteria, including 2,226 patients in the DOAC group and 5,936 in the no-OAC group. The major cardiovascular ischemic event was significantly lower in the DOAC group [OR = 0.11; CI 95% (0.03, 0.45); p = 0.002]. Ischemic stroke was lower in the DOAC group [OR = 0.53, 95% CI (0.39–0.72), p < 0.001]. There was no difference in ICH recurrence [OR = 1.25, 95% CI (0.28–5.71), p = 0.77] or major bleeding [OR = 0.63, 95% CI (0.23–1.72), p = 0.36]. Mortality rates were similar between groups [OR = 0.75, 95% CI (0.50–1.11), p = 0.15], while Heterogeneity was low for most outcomes.ConclusionDOACs appear to reduce the risk of IS without increasing mortality or major bleeding in patients with atrial fibrillation and prior ICH. However, the risk of ICH recurrence remains uncertain. These findings suggest a potential role for DOACs in this high-risk population, but further RCTs are needed to confirm these results.Systematic review registrationIdentifier CRD42024587511.